Processed airborne radio-echo sounding data from the WISE-ISODYN survey across the Wilkes Subglacial Basin, East Antarctica (2005/2006) - Ferraccioli, Fausto; Corr, Hugh; Jordan, Tom; Robinson, Carl; Armadillo, Egidio; Bozzo, E.; Caneva, G. (NERC EDS UK Polar Data Centre, 2021)
During the austral summer of 2005/06 a collaborative UK/Italian field campaign collected ~61,000 line km of aerogeophysical data over the previously poorly surveyed Wilkes subglacial basin, Dome C, Transantarctic Mountains, George V Land and Northern Victoria Land using airborne survey systems mounted in a Twin Otter aircraft. Our aircraft was equipped with dual-frequency carrier-phase GPS for navigation, radar altimeter for surface mapping, wing-tip magnetometers, a LaCoste and Romberg air-sea gravimeter, and an ice-sounding radar system (PASIN). We present here the full radar dataset consisting of the deep-sounding chirp and shallow-sounding pulse-acquired data in their processed form, as well as the navigational information of each trace, the surface and bed elevation picks, ice thickness, and calculated absolute surface and bed elevations. This dataset comes primarily in the form of NetCDF and georeferenced SEGY files. To interactively engage with this newly-published dataset, we also created segmented quicklook PDF files of the radar data. : ** Instrumentation and Processing: Radar data were collected using the bistatic PASIN radar echo sounding system mounted on the BAS Twin Otter aircraft "VP-FBL" and operating with a centre frequency of 150 MHz and using two interleaved pulses: a 4-microseconds, 10 MHz bandwidth linear chirp (deep sounding) and a 0.1-microseconds unmodulated pulse (shallow sounding). Chirp compression was applied using a Blackman window to minimise sidelobe levels, resulting in a processing gain of 10 dB. The chirp data was processed using an coherent averaging filter (commonly referred to as unfocused Synthetic Aperture Radar (SAR) processing) along a moving window of length 33. This product is best used to assess the bed and internals in deep ice conditions. The pulse data was processed using an incoherent averaging filter and using a combination of the upper and lower channels. This data is best used to assess the internal structure and bed in shallow ice conditions. The bed reflector was first automatically depicted on the chirp data using a semi-automatic picker in the PROMAX software package. All the picks were afterwards checked and corrected by hand if necessary. The picked travel time was then converted to depth using a radar wave speed of 168 m/microseconds and a constant firn correction of 10 m. Surface elevation is derived from radar altimeter for ground clearance < 750 m, and the PASIN system for higher altitudes. ** Coordinates and Positions: The coordinates provided in the NetCDF for the surface and bed elevation for each radar trace are in longitude and latitude (WGS84, EPSG: 4326). The navigation attributes for the radar data in the NetCDF are in projected X and Y coordinates (Polar Stereographic, EPSG: 3031), as follows: Latitude of natural origin: -71 Longitude of natural origin: 0 Scale factor at natural origin: 0.994 False easting: 0 False northing: 2082760.109 The coordinates in the SEGY data are also in projected X and Y coordinates (Polar Stereographic, EPSG: 3031), although note that these are in integer format due to the SEGY limitations (see section below). Positions are calculated for the phase centre of the aircraft antenna. All positions (Longitude, Latitude and Height) are referred to the WGS1984 ellipsoid. ** Dataset: Please note: Due to the unstable nature of SEGY-formatted data and its uncertain long-term future, as well as the issues documented below, we also provide the full radar data in NetCDF format. The dataset provided here consists of three parts: a NetCDF file per flightline, two SEGY files per flightline (one chirp and one pulse), and one quicklook PDF file per flightline. These are described in more details below. - NetCDF: The NetCDF files contain the deep-sounding chirp and shallow-sounding pulse-acquired data in their processed form, as well as the associated metadata, navigational information (in both EPSG: 3031 and WGS84 EPSG: 4326), and the associated radar-related information for each trace (e.g. surface/bed elevation and picks, ice thickness, aircraft altitude, range to surface, time of trace) which are provided as separate attributes in the NetCDF file. The navigational position of each trace comes from the surface files, and the processed GPS files when no surface information was provided in the surface files. Note that for these, interpolation of the navigational data might have been required to match closely the Coordinated Universal Time (UTC) of each trace in the surface files. No data is shown as "-9999" throughout the files. NetCDF attributes: - 'traces': Trace number for the radar data (x axis) - 'fast_time': Two-way travel time (y axis) (units: microseconds) - 'x_coordinates': Cartesian x-coordinates for the radar data (x axis) (units: meters in WGS84 EPSG:3031) - 'y_coordinates': Cartesian y-coordinates for the radar data (x axis) (units: meters in WGS84 EPSG:3031) - 'chirp_data': Radar data for the processed (coherent) chirp (units: power in dBm) - 'pulse_data': Radar data for the processed (incoherent) pulse (units: power in dBm) - 'longitude_layerData': Longitudinal position of the trace number (units: degree_east in WGS84 EPSG:4326) - 'latitude_layerData': Latitudinal position of the trace number (units: degree_north in WGS84 EPSG:4326) - 'UTC_time_layerData': Coordinated Universal Time (UTC) of trace (also known as resTime) (units: seconds) - 'PriNumber_layerData': Incremental integer reference number related to initialisation of the radar system that permits processed SEGY data and picked surface and bed to be linked back to raw radar data (also known as PriNum) (units: arbitrary - integers) - 'terrainClearanceAircraft_layerData': Terrain clearance distance from platform to air interface with ice, sea or ground (also known as resHt) (units: meters) - 'aircraft_altitude_layerData': Aircraft altitude (also known as Eht) (units: meters relative to WGS84 ellipsoid) - 'surface_altitude_layerData': Ice surface elevation for the trace number from radar altimeter and LiDAR (units: meters relative to WGS84 ellipsoid) - 'surface_pick_layerData': Location down trace of surface pick (BAS system) (units: microseconds) - 'bed_altitude_layerData': Bedrock elevation for the trace number derived by subtracting ice thickness from surface elevation (units: meters relative to WGS84 ellipsoid) - 'bed_pick_layerData': Location down trace of bed pick (BAS system) (units: microseconds) - 'land_ice_thickness_layerData': Ice thickness for the trace number obtained by multiplying the two-way travel-time between the picked ice surface and ice sheet bed by 168 m/microseconds and applying a 10 meter correction for the firn layer (units: meters) - SEGY: The SEGY files are provided for both the chirp and pulse-acquired data and have been georeferenced using the navigational position of each trace from the surface files, and the processed GPS files when no surface information was provided in the surface files. Note that for these, interpolation of the navigational data might have been required to match closely the Coordinated Universal Time (UTC) of each trace in the surface files. SEGY header description: - byte number 1-4 and 5-8 (SEQWL and SEQWR): Trace number for each SEGY trace - byte number 9-12 (FFID): PriNumber for each SEGY trace - byte number 73-76 (SRCX): Cartesian x-coordinates for each SEGY trace (units: meters in WGS84 EPSG:3031) - byte number 77-80 (SRCY): Cartesian y-coordinates for each SEGY trace (units: meters in WGS84 EPSG:3031) - byte number 115-116 (NSMP): Number of samples for each SEGY trace - byte number 117-118 (SI): Sampling interval for each SEGY trace Note that the current version of the SEGY (Revision 1.0) does not yet allow to store double-precision floats in the "Source X/Y" trace headers and thus the X and Y positions for each trace are rounded to the nearest integer when exporting the data. This will affect the accurate position of each trace in the SEGY data, however the precise X and Y position of each trace can be obtained from the NetCDF files if necessary. When loading in the georeferenced SEGY files into seismic-interpretation software for data visualisation and analysis, the user might be warned that duplicate traces are found within the data and that this might cause "bad performance". This is caused by the rounding of the X and Y positions in the SEGY headers as explained above and should only affect the position of a relatively small amount of traces. - Quicklook: The quicklook PDF files were produced to allow for a quick visualisation of the radar data and the position of each flightline with regards to the rest of the survey flightlines. The radar image in the PDF is from the processed chirp radar data and is split into 50-km segments for the WISE-ISODYN survey. These segments (and the radar images associated with them) are the same as those shown on the Polar Airborne Geophysics Data Portal. : ** Instrument: Radar data were collected using the bistatic PASIN (Polarimetric radar Airborne Science Instrument) radar echo sounding system mounted on the BAS Twin Otter aircraft "VP-FBL" and operating with a centre frequency of 150 MHz and using two interleaved pulses: a 4-microseconds, 10 MHz bandwidth linear chirp (deep sounding) and a 0.1-microseconds unmodulated pulse (shallow sounding). The Pulse Repetition Frequency was 15,635 Hz (pulse repetition interval: 64 microseconds). ** Antenna configuration: 8 folded dipole elements: 4 transmitters (port side) 4 receivers (starboard side) Antenna gain: 11 dBi (with 4 elements) Transmit power: 1 kW into each 4 antennae Maximum transmit duty cycle: 10% at full power (4 x 1 kW) ** Radar receiver configuration: Receiver vertical sampling frequency: 22 MHz (resulting in sampling interval of 45.4546 ns) Receiver coherent stacking: 25 Receiver digital filtering: -50 dBc at Nyquist (11 MHz) Effective PRF: 312.5 Hz (post-hardware stacking) Sustained data rate: 10.56 Mbytes/second : - Trace spacing (post-processed data): ~20 m - Vertical resolution: ~8.4 m - Radar centre frequency: 150 MHz - Radar bandwidth: 10 MHz - Radar Receiver vertical sampling frequency: 22 MHz - Absolute GPS positional accuracy: ~0.1 m (relative accuracy is one order of magnitude better). Banking angle was limited to 10 degrees during aircraft turns to avoid phase issues between GPS receiver and transmitter. The line spacing for the main survey area is 8.8 km, with tie lines 44 km apart. Additional regional lines explore specific targets.The standard deviation of the bed elevation for all crossover errors for the radar data is 33.3 m. However, this value is skewed by a few high error points in regions of more extreme topography. Over areas with smoother topography the standard deviation of the crossovers is ~10 m. Please note: The surface and bed pick information (surface and bed elevation, ice thickness, etc.) can also be found at:https://doi.org/10.5285/59e5a6f5-e67d-4a05-99af-30f656569401.The datasets found here have been considerably curated and improved, and thus can be considered the latest and full dataset.